2014
DOI: 10.1007/s00128-014-1224-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bromothalonil Residues and Degradation in Apple and Soil by QuEChERS and GC–MS/MS

Abstract: The dissipation and residues of bromothalonil in apple and soil under field condition were analyzed by QuEChERS (quick, easy, cheap, effective, rugged and safe) combined with gas chromatography-mass spectrometer method. The recoveries were ranged from 80.8 % to 106 % with coefficient variation for repeatability ranged from 3.08 % to 7.09 % at fortification levels of 0.02, 0.04 and 0.2 mg/kg in apple and soil. The limit of quantification of the method was 0.31 lg/kg. The dissipation rates of bromothalonil follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The half‐life values of bromothalonil degradation ranged from 7.14 to 24.75 days in tomato, cucumber, chieh‐qua and soil. Previous studies showed that the half‐life values of bromothalonil degradation ranged from 3.61 to 3.98 days in apple and from 7.8 to 14.9 days in tobacco . According to the Chinese National Standard GB/T 31270.1–2014, bromothalonil is an easily degraded pesticide (half‐life values < 30 days).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The half‐life values of bromothalonil degradation ranged from 7.14 to 24.75 days in tomato, cucumber, chieh‐qua and soil. Previous studies showed that the half‐life values of bromothalonil degradation ranged from 3.61 to 3.98 days in apple and from 7.8 to 14.9 days in tobacco . According to the Chinese National Standard GB/T 31270.1–2014, bromothalonil is an easily degraded pesticide (half‐life values < 30 days).…”
Section: Resultsmentioning
confidence: 99%
“…In the agricultural arena, bromothalonil is found in fungicides, herbicides and bactericides. It was registered and promoted for use in 2008 in China, where it is widely used on fruits and vegetables to control anthracnose disease …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations